The role of CdS nanofiller on improved vibrational, structural and mechanical properties of CdS/PVA nanocomposite films fabricated through precipitation-casting approach - Chan Kok Sheng; Yousef Mohammad Alrababah (South African Journal of Chemical Engineering)
In this work, CdS/PVA nanocomposite films were synthesized via the precipitation-casting method by embedding different quantities of CdS nanofillers (by weight%) into the PVA polymeric matrix. The samples were characterized by XRD, FTIR, SEM, EDS, and a universal testing machine (UTM). XRD analysis dictates that the crystallinity enhances by increasing the CdS content in the composite, with a sharper and dominant peak observed at 2θ = 21°, implying a stronger interaction occurred between CdS nanoparticles and PVA molecular chains. The EDS spectra show two major peaks representing Cd and S elements due to a homogeneous distribution of CdS nanoparticles over the composite surface. The formation of CdS nanoparticles is further confirmed by FTIR analysis, which shows a distinctive peak located at 708 cm−1 that represents the Cd-S stretching vibrational bonds. Meanwhile, the IR spectra also reveal that an effective interaction with a well-organized coordination has occurred between CdS and PVA. SEM images reveal that the CdS nanoparticles, with an average size of around 80–100 nm, are homogeneously dispersed over the PVA matrix surface. However, the CdS nanofillers tend to agglomerate into larger-size particles as the CdS content increases. The mechanical tensile properties of Young's modulus, stress and strain at break enhance as the CdS dosage increases in the composite, which could be attributed to an increase in uniformity of particle distribution that in turn improves the interaction between CdS and PVA, as evidenced by SEM and FTIR analysis.